Is the association of deliberate self-harm with emotional relief stable or dependent on emotional context?. (September 2018) - Gratz, Kim L.; Tull, Matthew T.; Dixon-Gordon, Katherine L.; Turner, Brianna J.; Chapman, Alexander L.
Abstract: Background and objectives: Despite strong support for the role of emotional relief in deliberate self-harm (DSH), no research has examined the impact of emotional distress on the strength of the DSH-relief association. Thus, it remains unclear whether the association of DSH with emotional relief is stable across emotional contexts or context-dependent. This study aimed to examine if the implicit DSH-relief association is stronger in the context of emotional distress (relative to a neutral emotional context). Methods: Young adult women with (n = 60) and without (n = 60) a history of recent recurrent DSH were randomly assigned to complete a novel version of the Implicit Association Test (IAT) assessing the DSH-relief association at baseline (following an initial neutral emotion induction) and again following either a neutral or negative (i.e., social rejection) emotion induction. Results: Consistent with hypotheses, the DSH-relief association was stronger among women with recent recurrent DSH (vs. those without DSH) at baseline. Contrary to hypotheses, however, whereas the DSH-relief association remained stable following both the neutral and negative emotion inductions among participants with DSH, it became stronger across both conditions for participants without DSH. Limitations: The use of a community sample of young adult women may limit generalizability to other relevant populations (e.g., clinical populations, young men, adolescents). Additionally, the negative emotion induction may not have been powerful enough to affect the strength of the learned DSH-relief association among individuals with a repeated history of DSH. Conclusions: Findings suggest that the repeated use of DSH to bring about emotional relief may engender associations of DSH with relief that are relatively insensitive to emotional context. Highlights: Research shows that deliberate self-harm (DSH) is associated with emotional relief. It remains unclear if the DSH-relief association is stable or context-dependent. We examined this association in both neutral and negative emotional contexts. The DSH-relief association was stable across emotional contexts for women with DSH.